2006
DOI: 10.1007/s11259-005-3227-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Flunixin after Intravenous Administration in Healthy and Endotoxaemic Rabbits

Abstract: The pharmacokinetics of flunixin were determined after intravenous bolus injection at a single dose (2.2 mg/kg) in healthy rabbits and diseased rabbits with Escherichia coli lipopolysaccharide-induced septic shock. Six adult New Zealand White rabbits were used. Concentrations of drug in plasma were determined by HPLC. Pharmacokinetics were best described by a two-compartment open model. In healthy rabbits, there was a high plasma clearance (0.62 L/(h kg)), and a relatively short elimination half-life (1.19 h).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
20
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 33 publications
6
20
4
Order By: Relevance
“…Total protein, albumin, glucose, creatinine, BUN, Ca, P, Na, K and Cl levels determined in this study and presented in Table 2 were within the range of reference values reported for rabbits in previous studies (Yu et al, 1979;Hewitt et al, 1989;Lepitzki and Woolf, 1991;Yazar et al, 2004;Silva et al, 2005;Elmas et al, 2006;Melillo, 2007). No statistically significant difference for any parameters, except serum K concentration, was determined in this study between male and female rabbits.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Total protein, albumin, glucose, creatinine, BUN, Ca, P, Na, K and Cl levels determined in this study and presented in Table 2 were within the range of reference values reported for rabbits in previous studies (Yu et al, 1979;Hewitt et al, 1989;Lepitzki and Woolf, 1991;Yazar et al, 2004;Silva et al, 2005;Elmas et al, 2006;Melillo, 2007). No statistically significant difference for any parameters, except serum K concentration, was determined in this study between male and female rabbits.…”
Section: Discussionsupporting
confidence: 85%
“…Serum GGT activity was higher than was found in other studies (Yu et al, 1979;Hewitt et al, 1989;Tavares et al, 2004;Yazar et al, 2004;Elmas et al, 2006;Melillo, 2007). AST activity was near to the levels reported in some previous studies (Yu et al, 1979;Tavares et al, 2004) and lower than the levels observed in some others (Lepitzki and Woolf, 1991;Silva et al, 2005;Elmas et al, 2006;Melillo, 2007).…”
Section: Discussioncontrasting
confidence: 48%
“…In the present study, CCl 4 treatment induced apparent liver dysfunction without renal damage, and glycerol treatment induced marked renal dysfunction with little liver injury. These results are mostly consistent with the previous studies [5,10]. Therefore, our results confirm that CCl4 and glycerol treatment induce selective hepatic and renal dysfunction.…”
Section: -Note-supporting
confidence: 93%
“…Flunixin acts through the inhibition of cyclooxygenase, which synthesizes prostaglandins from arachidonic acid [12]. Flunixin has been used for the control of postoperative pain and the treatment of respiratory diseases, mastitis, osteoarthritis, and endotoxemia in a variety of animals [2,6,11]. Pharmacokinetic profiles of flunixin are characterized by good bioavailability, short half-life and a high protein binding property.…”
mentioning
confidence: 99%
“…However, this value slightly increased in coadministration of FF-FM-LPS and FF-TN-LPS when compared with FF-LPS in animal groups. As a result, increasing the AUC (0)(1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and lengthening the t 1/2λz may be related to decreasing the Cl T of FF in coadministered groups in endotoxemic rabbits. In our study, the V ss of FF was large (from 1.85 ± 0.12 to 2.21 ± 0.06 L/kg).…”
Section: Discussionmentioning
confidence: 99%